Omalizumab reduces bronchial mucosal IgE and improves lung function in non-atopic asthma. Issue 6 (20th October 2016) - Pillai, Prathap; Chan, Yih-Chih; Wu, Shih-Ying; Ohm-Laursen, Line; Thomas, Clare; Durham, Stephen R.; Menzies-Gow, Andrew; Rajakulasingam, Raj K.; Ying, Sun; Gould, Hannah J.; Corrigan, Chris J.
Omalizumab therapy of non-atopic asthmatics reduces bronchial mucosal IgE and inflammation and preserves/improves lung function when disease is destabilised by staged withdrawal of therapy. 18 symptomatic, non-atopic asthmatics were randomised (1:1) to receive omalizumab or identical placebo treatment in addition to existing therapy for 20 weeks. Bronchial biopsies were collected before and after 12–14 weeks of treatment, then the patients destabilised by substantial, supervised reduction of their regular therapy. Primary outcome measures were changes in bronchial mucosal IgE + cells at 12–14 weeks, prior to regular therapy reduction, and changes in lung function (forced expiratory volume in 1 s) after destabilisation at 20 weeks. Quality of life was also monitored. Omalizumab but not placebo therapy significantly reduced median total bronchial mucosal IgE + cells (p<0.01) but did not significantly alter median total mast cells, plasma cells, B lymphocytes, eosinophils and plasmablasts, although the latter were difficult to enumerate, being distributed as disperse clusters. By 20 weeks, lung function declined in the placebo-treated patients but improved in the omalizumab treated patients, with significant differences in absolute (p=0.04) and % predicted forced expiratory volume in 1 s (p=0.015). Omalizumab therapy of non-atopic asthmatics reduces bronchial mucosal IgE + mast cells and improves lung function despite withdrawal of conventional therapy. Omalizumab reduces mucosal IgE and improves lung function in non-atopic asthma http://ow.ly/CHFu3034fcC